The occupational anxiety of teachers caused by China’s ‘double reduction’ policy—a study based on the grounded theory - Yue, Wei; Yu, Le; Yang, Yanru (Frontiers in Psychology, 2023)
Teachers’ occupational anxiety is a kind of negative emotional state of teachers, which is prevalent in Chinese teachers. Unfortunately, in the existing research, teachers’ occupational anxiety caused by China’s ‘double reduction’ policy has not been paid attention to. Based on the grounded theory, this study conducted in-depth interviews with 45 in-service primary and junior high school teachers, and used NVivo 12 to process recording materials. Through a series of steps such as open coding, axial coding and selective coding, we found that the core feature of teachers’ occupational anxiety caused by the ‘double reduction’ policy was that the implementation of the ‘double reduction’ policy was incomplete matching the actual educational ecology. Then we constructed a theoretical model of the formation mechanism of teachers’ occupational anxiety caused by the ‘double reduction’ policy. The study showed that due to the influence of teachers’ own personality characteristics and incomplete match between external factors, although teachers insisted on self-adjustment, it was difficult to fundamentally solve the teachers’ occupational anxiety caused by the ‘double reduction’ policy.